A stronger reversal effect of the combination of dasatinib and menadione on P-gp-mediated multidrug resistance in human leukemia K562/Adr cell line. Issue 28 (21st March 2017) - Wang, Changyuan; Liu, Zhihao; Sun, Yaoting; Chen, Ting; Huo, Xiaokui; Meng, Qiang; Liu, Qi; Sun, Huijun; Sun, Pengyuan; Peng, Jinyong; Ma, Xiaodong; Liu, Kexin
Abstract : Multidrug resistance (MDR) leads to poor efficiency of chemotherapy. Abstract : Multidrug resistance (MDR) leads to poor efficiency of chemotherapy. Overexpression of membrane transporters including P-gp could result in MDR. In this study, we investigated the effect of the combination of dasatinib (DA) and menadione (MQ) on P-gp-mediated MDR in the human leukemia K562/Adr cell line. The combination of DA and MQ had a stronger effect on potentiating the sensitivity of K562/Adr cells to DOX and reducing the formation of cell colonies, further increasing the accumulation of DOX and rhodamine 123 in P-gp-overexpressing K562/Adr cells. The increasing cellular accumulation of DOX led to the enhanced increase of DOX-induced and caspase-3-mediated cell apoptosis via ROS production. The stronger reversal effect of the combination of DA and MQ might partly be due to the increased downregulation of mRNA and protein levels of P-gp as opposed to direct inhibition of the P-gp efflux ability. However, the ERK and AKT/mTOR signal pathways were not involved. The combination of DA and MQ shows potential advantages in overcoming MDR in cancer chemotherapy.